Tax and Non-tax Revenue of the Budget: What’s the Difference? - KOMYAGIN, Dmitry L. (Journal of Advanced Research in Law and Economics, 2018)
The article discusses the nature of non-tax public revenue. The author first offers his own universal definition of public revenue. This results in the discovery of a variety of theoretical and practical problems, which include decentralized revenue, non-uniformity of non-tax revenue, and a contradiction involved in grouping certain forms of revenue together. A proposal is offered to consider public revenue in its various phases, initially as a based in national wealth, then as mobilized in the form of budget revenue, redistributed for public needs, and then administered.